Anestesi pada Nefrolitotomy - Dayanti Nuroazi Utari; Muhammad Rizki (Lembaga Pengembangan Kinerja Dosen, 2025)
Anesthesia is an act of relieving pain when performing surgery and various other procedures that cause pain in the body. Anesthesia procedures include pre-anesthesia, intra-anesthesia and post-anesthesia. Nephrolithiasis is very common, causing immense pain and incurring huge economic costs. It is known that nephrolithiasis can cause post-renal acute kidney injury (AKI) through obstruction of urine flow, which is often associated with rapid decline in renal function. Nephrolithiasis can be treated by pharmacologic means, laser treatment as well as radiologic stone crushing with the help of electromagnetic waves, and surgery (4). In surgical procedures such as open kidney general anesthesia is more recommended than regional anesthesia because the position of the patient can cause the patient to feel uncomfortable and pain arises from diaphragmatic stimulation.